2016
DOI: 10.1002/cam4.780
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of the ubiquitin ligase carboxyl terminus of the Hsc70‐interacting protein in postmenopausal breast cancer

Abstract: The carboxyl terminus of the Hsc70‐interacting protein (CHIP) is considered to induce the ubiquitination and degradation of several oncogenic proteins, and play a role in the inhibition of tumor progression and invasion under experimental conditions. However, the impact of CHIP expression on the prognosis of breast cancer patients has not yet been established. In this study, using an immunohistochemical method, 272 patients with invasive breast cancer were assessed for the expression of CHIP (graded scores 0‐3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…66,67 We previously demonstrated that strong CHIP expression is correlated with ER positivity, PgR positivity and HER2 negativity, and identified CHIP expression as a potent prognostic factor in postmenopausal patients with invasive breast cancer. 68 Ozgur et al 69 reported that two miRNAs, miR-29a and miR-193b, are associated with breast cancer through their contact with HSP70.…”
Section: Mirna In Hormone Receptor-positive/her2-negative Breast Cancermentioning
confidence: 99%
“…66,67 We previously demonstrated that strong CHIP expression is correlated with ER positivity, PgR positivity and HER2 negativity, and identified CHIP expression as a potent prognostic factor in postmenopausal patients with invasive breast cancer. 68 Ozgur et al 69 reported that two miRNAs, miR-29a and miR-193b, are associated with breast cancer through their contact with HSP70.…”
Section: Mirna In Hormone Receptor-positive/her2-negative Breast Cancermentioning
confidence: 99%
“…Even in ER-positive cases, the CpG9-methylated group showed no significant difference in recurrence rate compared to each of the ER-negative methylation groups. Previously, we reported the relationship between ER and CHIP protein expression (31), and recurrence-free survival was significantly better in the ER-positive cases with high CHIP expression than in ER-negative cases. However, although positive for ER, such cases with low CHIP expression tended to have worse recurrence-free survival than those with high CHIP expression.…”
Section: Discussionmentioning
confidence: 89%
“…Furthermore, El Ansari et al (2018) elucidated that high LAT1 expression levels are associated with high proliferation potential, as indicated by the high Nottingham Prognostic Index and Ki67 labeling index; high LAT1 expression levels are also a poor prognosis factor in luminal B-like type breast tumors. It has been postulated that luminal A-like and luminal B-like type tumors display signi cantly different proliferation abilities in ER-positive BCa (Kurozumi S et al 2016;Burstein H J et al 2019). Thus, a combinatorial chemotherapeutic approach is recommended because luminal B-like type tumors have an extremely high proliferation potential.…”
Section: Discussionmentioning
confidence: 99%